(2-Hydroxy-4-methoxyphenyl)(2-hydroxyphenyl)methanone - Betz, Richard (International Union of Crystallography, 2011)
The title compound, C(14)H(12)O(4), is an asymmetric substitution product of benzophenone. Both hydroxy groups are orientated towards the O atom of the keto group. Intramolecular as well as intermolecular O—H⋯O hydrogen bonds can be observed in the crystal structure, with the latter connecting the molecules into chains along the crystallographic b axis. C—H⋯O contacts [C⋯O = 3.3297 (18) Å] are also apparent. The closest centroid–centroid distance between two aromatic systems is 4.9186 (9) Å.